Th1 and Th17 Cytokines Drive Inflammation in Takayasu Arteritis. Issue 5 (May 2015) - Saadoun, D.; Garrido, M.; Comarmond, C.; Desbois, A. C.; Domont, F.; Savey, L.; Terrier, B.; Geri, G.; Rosenzwajg, M.; Klatzmann, D.; Fourret, P.; Cluzel, P.; et al.
<x xml:space="preserve">Abstract</x> Objective Takayasu arteritis (TAK) is a large‐vessel vasculitis that induces damage to the aorta and its branches. Glucocorticoids remain the gold standard of therapy for TAK. The nature of the T cells driving vascular inflammation and the effects of glucocorticoids on the systemic components of TAK are not understood. The aim of this study was to analyze T cell homeostasis and cytokine production in peripheral blood and inflammatory lesions of the aorta in patients with TAK. Methods T cell homeostasis and cytokine production in peripheral blood and inflammatory lesions of the aorta were analyzed using Luminex analysis, flow cytometry, and immunohistochemical analysis. The study included 41 patients fulfilling the American College of Rheumatology 1990 criteria for the classification of TAK (17 patients with active TAK and 24 patients with disease in remission), 30 patients with giant cell arteritis and 39 patients with Behçet's disease (disease controls), and 20 age‐ and sex‐matched healthy control subjects. Results We observed a marked increase in the expression of Th1 and Th17 cells, which correlated with TAK disease activity. The addition of serum from patients with active TAK to sorted CD4+ T cells from healthy donors in culture medium induced significant production of interferon‐γ (IFNγ) and interleukin‐17A (IL‐17A). We demonstrated the presence of IFNγ‐, IL‐6–, and IL‐17A–producing T cells in vascular inflammatory infiltrates in patients with TAK. Corticosteroid therapy was associated with decreased levels of circulating Th1 cytokines in corticosteroid‐treated patients with TAK compared with steroid‐free patients with TAK (for IL‐2, mean ± SD 5, 079 ± 5, 300 versus 7, 359 ± 3, 197 pg/ml; for IFNγ, 2, 592 ± 3, 072 versus 8, 393 ± 3, 392 pg/ml; for tumor necrosis factor α, 847 ± 724 versus 1, 491 ± 392 pg/ml). However, glucocorticoids had essentially no effect on the frequency of Th17 cytokines (IL‐1 receptor, IL‐17, and IL‐23). Conclusion The Th17 and Th1 pathways contribute to the systemic and vascular manifestations of TAK. Glucocorticoid treatment suppresses Th1 cytokines but spares Th17 cytokines in patients with TAK.